Saving Morality: A Case against Moral Neutralism - Zavaliy, Andrei (2012)
The purpose of this paper is to defend a position in metaethics, saving morality from certain reductionist attempts, and arguing that a moral point of view denotes a distinct attitude toward the world with a set of relatively stable conditions. I discuss the problem of demarcation between the moral and the non-moral domains, and contrast the two basic approaches – moral neutralism and moral descriptivism. Moral neutralism is defined as a view which builds no content requirements into the definition of moral rules, whereas moral descriptivism or essentialism places identifiable constraints on the content of an action-guiding principle if such a principle is to count as a moral, as opposed to a non-moral, rule. I show that adopting neutralism is tantamount to giving up ethical theory as a scholarly activity with a distinct subject matter altogether. It is further argued that W. Frankena’s essentialist definition of morality, as well as a more recent view of Catherine Wilson, share a similar weakness and fall short from neutralizing neutralism. Finally, I propose a modification to the essentialist account of morality, which would significantly increase the resilience of such an account to attempts of reducing moral prescriptions to any action-guiding policy whatsoever, as long as such policy is sincerely adhered to and followed consistently. The proposed modification is described as a Realism constraint, and it refers to the connection between one’s expectations of the outcome of observing a prohibition or following a certain rule and the actual consequences of following a given policy.